Effects of leaf extracts of Vernonia amygdalina on the force and rate of contractility of an isolated mammalian heart - Bbosa, Godfrey S.; Lubajo, Robert; Lubega, Aloysius M.; Odia, Gordon; Katerega, John (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Vernonia amygdalina is a common medicinal plant that is widely used by local communities and traditional herbalists in central Uganda in management of various conditions including hypertension that occurs as a result of changes in heart contractility. However, there is limited scientific information of V. amygdalina effects on the force and rate of contractility of the heart. The study evaluated the inotropic and chronotropic effect of methanol, aqueous, ether and total crude leaf extracts of V. amygdalina on isolated perfused rabbit heart. Methods: An experimental laboratory based study determined the effects of V. amygdalina extracts on the rate and force of contraction isolated perfused rabbit using the Langendorff’s heart perfusion experiment and methods. The heart rate (beats/minute) was counted per minute. The force of contraction of the heart was determined measuring the height of each peak on the kymogram. Results: The findings showed that the force and rate of heart contractility reduced with increasing doses of methanol, aqueous ether and total crude leaf extracts at doses of 0.5, 8.0, 62.0 and 250.0 mg/ml. The force and rate of heart contractility at a dose of 250.0 mg/ml for all the extracts were comparable to that of acetylcholine drug to almost causing cardiac arrest. Conclusions: The leaf extracts of V. amygdalina contain compounds that reduced the force and rate of contraction of an isolated rabbit heart.